Populism and Instrumentality: From Pathological Symptoms to Ontological Sinthomes for Educational Theory - Abdellatif Atif (Ars Educandi)
This contribution suggests a new reading of education's relationship with two problematic contemporary elements: populism and instrumentality. Usually, political and educational scientists portray populism as instrumentalizing education for goals outside its scope, while growing tendencies in educational philosophy go further to see education as heterogeneous with any instrumentality whatsoever. Both positions reduce the contingency, dislocation and antagonism that populism and instrumentality may inflict to education to an exceptional pathology that education can (should) bypass. By relying on Ernesto Laclau and Chantal Mouffe’s political ontology, this paper does not look at populism and instrumentality as antagonists to education only in how they are an external negativity disturbing education but also as symptoms of the internal negativity of education permitting its (re)articulation in the first place. The author estimates that this starting point can emancipate the study of education's relationship to populism and instrumentality from a simple description of scandalous states to an ontological investigation with epistemological and ethical results that touch more adequately on the urgent challenges of certain forms of populism and instrumentality to education.